Hypothalamic mTOR signaling mediates the orexigenic action of ghrelin. - Luís Martins (Public Library of Science (PLoS), 2012)
Current evidence suggests that ghrelin, a stomach derived peptide, exerts its orexigenic action through specific modulation of Sirtuin1 (SIRT1)/p53 and AMP-activated protein kinase (AMPK) pathways, which ultimately increase the expression of agouti-related protein (AgRP) and neuropeptide Y (NPY) in the arcuate nucleus of the hypothalamus (ARC). However, there is a paucity of data about the possible action of ghrelin on alternative metabolic pathways at this level. Here, we demonstrate that ghrelin elicits a marked upregulation of the hypothalamic mammalian target of rapamycin (mTOR) signaling pathway. Of note, central inhibition of mTOR signaling with rapamycin decreased ghrelin's orexigenic action and normalized the mRNA expression of AgRP and NPY, as well as their key downstream transcription factors, namely cAMP response-element binding protein (pCREB) and forkhead box O1 (FoxO1, total and phosphorylated). Taken together, these data indicate that, in addition to previous reported mechanisms, ghrelin also promotes feeding through modulation of hypothalamic mTOR pathway.